Flavonol Glycosides from Eugenia uniflora Leaves and Their In Vitro Cytotoxicity, Antioxidant and Anti-Inflammatory Activities - Ayodeji Oluwabunmi Oriola; Gugulethu Mathews Miya; Moganavelli Singh; Adebola Omowunmi Oyedeji (MDPI AG, 2023)
In view of the extensive use of Eugenia uniflora leaves for the management of tumours and other chronic inflammatory diseases in traditional medicine, an activity-guided fractionation of its leaf ethanolic extract led to the isolation of two flavonol glycosides. Cytotoxicity study was based on the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) viability assay against the non-tumourigenic human embryonic kidney (HEK-293) cells, and the cancerous liver (Hep-G2) and cervical (HeLa) cell lines. Antioxidant tests were carried out using 2,2-diphenyl-1-picrylhydrazyl (DPPH), nitric oxide (NO) and hydrogen peroxide (H2O2) radical scavenging assays, while an in vitro anti-inflammatory test was conducted using egg albumin denaturation (EAD) assay. Based on comprehensive spectroscopic and spectrometric evidence, the compounds were elucidated as myricitrin (1) and a newly described compound, 5,7-dihydroxy-3-(3,4,5-trihydroxy-6-methyltetrahydropyran-2-yloxy)-2-(2,4,5-trihydroxyphenyl)chromen-4-one, named "unifloratrin (2)". The cytotoxicity of myricitrin (1) was comparable to 5-fluorouracil (standard drug), with a CC50 of 8.5 ± 2.2 µg/100 µL against HeLa cells. It also demonstrated better antioxidant activity, with an IC50 of 6.23 ± 1.09, 22.01 ± 2.59 and 30.46 ± 1.79 µM against DPPH, NO and H2O2 free radicals, respectively. At 20 µg/mL and an incubation time of 2 h, myricitrin was comparable to diclofenac (standard drug) in anti-inflammatory activity. This report may serve as a justification for the ethnomedicinal use of E. uniflora, while flavonol glycosides, such as myricitrin (1), could be further exploited as a candidate cytotoxic agent.